Using the expression, x+23, complete the table finding the value of y.

1 answer

To find the value of y, we need to substitute different values for x into the expression x+23 and evaluate the expression.

Let's create a table:

|x | y = x + 23 |
|---|---|
| 0 | 0 + 23 = 23 |
| 1 | 1 + 23 = 24 |
| 2 | 2 + 23 = 25 |
| 3 | 3 + 23 = 26 |

Thus, the completed table would look like this:

|x | y = x + 23 |
|---|---|
| 0 | 23 |
| 1 | 24 |
| 2 | 25 |
| 3 | 26 |

So, the values of y for each value of x are 23, 24, 25, and 26.